Eurocritical A Crisis of the Euro Currency - Macdonald, Roderick (Palgrave Macmillan UK, 2018)
This book critically analyses the crisis of the euro currency from 2008 to the present. It argues that an understanding of this crisis requires an understanding of financial and economic crises in individual countries participating in the euro. It goes on to describe and explain the crises in four countries - Greece, Ireland, Spain and Italy - showing how they differ and together challenge the euro currency by requiring a varied policy response from Europe. Eurocritical is a guide for scholars, students and practitioners of finance and economics.